Professional Competency of Secondary School Teachers and Classroom Learning Environment; A Correlational Study - Dr. Mehwiah Habib; Dr. Maksal Minaz; Ghazala Naheed Baig (Dialogue Social Science Review (DSSR), 2025)
The study correlate the variable of professional competency of teaches and the classroom learning environment at secondary level. For the selection of the respondents Simple random sampling technique was used. The respondents were comprised of 282 secondary school teachers, and 380 matric class (boys) students, 642 respondents from the three districts of Khyber Pakhtunkhwa. Three research objectives were created for the study. Learning environment Questionnaire (LEQ) was used to collect the related data. The instruments were validated through Cronbach’s alpha with the index of .938 which was obtained for the (LEQ) respectively. The data was collected and were analyzed using SPSS. Furthermore mean score, Pearson Product Moment Correlation statistic results were tested at 0.05 level of significance. The research study's findings indicated that most secondary school teachers possess the skills to create a friendly atmosphere in the classroom during the teaching and learning process. The findings revealed that a substantial relationship exists between teachers' understanding of Professional competency of secondary school teachers and the Classroom Learning Environment at secondary level. On the basis of the conclusions it was recommended that classroom atmosphere for learning should be engaging, and teachers are advised to utilize various resources tailored to their students' needs, including charts and audiovisual aids. Ease to access the technological resources that Students can utilize the technological tools to enhance their learning capabilities. It was recommended that educators make use of the teaching and learning resources accessible in classrooms to improve students' learning results. It was recommended that teachers in secondary schools should receive training to utilize instructional materials more effectively, enabling students to organize the content by the end.